Liquidity Risk Management of Mudharabah Deposit Products At PT. BPRS Al Makmur - Ifelda Nengsih; Rizal Rizal (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
Abstract This research aims to uncover the risk management and management system carried out by PT. BPR Syariah Al-Makmur against mudharabah deposit products. This type of research is qualitative with descriptive methods. Data is collected through interviews and documentation to get an overview of the research. This study found that deposits became a superior product because deposits could take funds even if they were not due and were not subject to fines (penalties). To avoid liquidity risks due to withdrawal of funds before maturity, management develops various strategies. The liquidity risk management strategy developed in sequence is through a persuasive approach, namely by giving ababa, requesting 1 to 3 days if the funds are insufficient and providing facilities for the delivery of funds to the customer's residence. The preventive strategy of handling liquidity risk is to predict the needs of funds by carrying out daily monitoring of funds so that the stock of funds is carried out, also through the asset liquidity approach and repressive approach. Become a new model of deposit management carried out by PT. BPR Syariah Al-Makmur because no other financial institution has done anything like this. This model proved to be the largest source of funds compared to ordinary savings from 2012 to 2018. Although the number of deposits has decreased from 2017 to 2019. Even in 2019 the number of deposits is lower than ordinary savings, but this is an interesting thing to study further why this can happen.